Validation of a short version of the high-fidelity simulation satisfaction scale in nursing students - Alejandro Martínez-Arce; Julián Rodríguez-Almagro; Esperanza Vélez-Vélez; Paloma Rodríguez-Gómez; Alberto Tovar-Reinoso; Antonio Hernández-Martínez (BMC, 2023)
Abstract Background Clinical simulation provides a practical and effective learning method during the undergraduate education of health professions. Currently there is only one validated scale in Spanish to assess nursing students' satisfaction with the use of high-fidelity simulation, therefore, our objective is to validate a brief version of this scale in undergraduate nursing students with or without clinical experience. Method A cross-sectional descriptive study was performed. Between 2018 and 2020, the students from all academic courses of the Fundación Jiménez Díaz nursing school completed the satisfaction scale at the end of their simulation experiences. To validate this scale, composed of 33 items and eight dimensions, exploratory factor analysis (EFA) of the principal components was performed, the internal consistency was studied using Cronbach's alpha, and the corrected item-test correlation of each of the items of the total scale was reviewed. Results 425 students completed the scale, after the exploratory factor analysis, a scale consisting of 25 items distributed into six subscales, each containing between two and six items, explained a variance of 66.5%. The KMO test (Kaiser-Meyer-Olkin) obtained a value of 0.938, Bartlett's sphericity test was < 0.01 and Goodness of Fit Index (GFI) was 0.991. Conclusion The modified ESSAF scale, reduced from 33 to 25 items and divided into six subscales, is as valid and reliable as the original scale for use in nursing students of different levels, with, or without clinical experience.